2022
DOI: 10.1093/hr/uhab036
|View full text |Cite
|
Sign up to set email alerts
|

Variation burst during dedifferentiation and increased CHH-type DNA methylation after 30 years of in vitro culture of sweet orange

Abstract: Somaclonal variation arising from tissue culture may provide a valuable resource for the selection of new germplasm, but may not preserve true-to-type characteristics, which is a major concern for germplasm conservation or genome editing. The genomic changes associated with dedifferentiation and somaclonal variation during long-term in vitro culture are largely unknown. Sweet orange was one of the earliest plant species to be cultured in vitro and induced via somatic embryogenesis. We compared four sweet orang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…There have also been cases where methylation levels initially decrease in early generations and then recover over longer periods of time, as shown in sweet orange after 30 years (X. Wang et al, 2022). Considering that our study is the first investigation of the cannabis methylome, it is plausible that methylation patterns stabilized in our clonal population over several subcultures.…”
Section: Methylation Variation In Cannabis Clonesmentioning
confidence: 73%
“…There have also been cases where methylation levels initially decrease in early generations and then recover over longer periods of time, as shown in sweet orange after 30 years (X. Wang et al, 2022). Considering that our study is the first investigation of the cannabis methylome, it is plausible that methylation patterns stabilized in our clonal population over several subcultures.…”
Section: Methylation Variation In Cannabis Clonesmentioning
confidence: 73%
“…Some studies have reported increases in methylation levels during subculturing ( Rival et al., 2013 ; Fraga et al., 2016 ), while others have observed decreases ( Xu et al., 2004 ; Huang et al., 2012 ; Machczyńska et al., 2014 ) over different subculturing durations. There have also been cases where methylation levels initially decrease in early generations and then recover over longer periods of time, as shown in sweet orange after 30 years ( Wang et al., 2022 ). Considering that our study is the first investigation of the cannabis methylome, it is plausible that methylation patterns stabilized in our clonal population over several subcultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that these techniques only study a small portion of the genome, which may not fully re ect the true extent of genetic variation. Wang et al (2022) recently reported the use of next-generation sequencing (NGS) to compare four sweet orange callus samples after 30 years of constant tissue culture with newly induced callus, providing new insights into assessing genetic variation. In our present study, we performed SNPs and InDels analysis using NGS, by sequencing the entire Raspberry 'Stiora' genome.…”
Section: Discussionmentioning
confidence: 99%